Assessing microbial diversity in Yellowstone National Park hot springs using a field deployable automated nucleic acid extraction system - Wood, Jason M.; Urbaniak, Camilla; Parker, Ceth; Singh, Nitin Kumar; Wong, Season; Arumugam, Arunkumar; Skorupa, Dana J.; Hemmah, Ashlyn; Laaguiby, Phoebe; Karouia, Fathi; Peyton, Brent M.; Tighe, Scott; et al. (Frontiers in Ecology and Evolution, 2024)
Microbial diversity estimation involves extracting nucleic acids from intricate sample matrices. Preparing nucleic acid samples is time-consuming, necessitating effective cell lysis and obtaining pure, inhibitor-free nucleic acid purifications before further use. An automated system offers advantages for field deployment due to its ease of use and quick autonomous results. This is especially beneficial for rapid measurement of in situ microbial diversity in remote areas. Our study aimed to assess microbial diversity of Yellowstone hot springs using a field-deployable lab in a resource-limited remote setting and demonstrate on-site nucleic acid sample processing and sequencing. We collected microbial mat and sediment samples from several Yellowstone National Park hot springs, focusing on the Five Sister Springs (FSS), spring LNN010, and Octopus Spring (OS). The samples were processed for DNA extraction on-site and further sequenced in the lab for microbial diversity. In addition, DNA extracted from one sample was sequenced and analyzed on-site as proof-of-concept. Using either Illumina or Oxford Nanopore Technology sequencing, we found similar microbial diversities. Bacteria (over 90%) were predominant at the FSS and OS sites, with archaea accounting for less than 10%. Metagenomic results were taxonomically categorized based on the closest known organism with a sequenced genome. The dominant archaeal community member was Candidatus Caldiarchaeum subterraneum, and among bacteria, Roseiflexus sp. RS-1 was abundant in mat samples. Interestingly, Bacterium HR17 was also frequently found, suggesting the need for more research on this newly recognized bacterial community member. The presence of Bacterium HR17 in these hot springs suggests its potential role in nitrogen cycling, informing both ecological understanding and industrial potential. This pioneering study assessed the microbiome of Yellowstone hot springs in about 8-9 hours using an automated system for nucleic acid extraction. By its deployment, the system's value in elucidating the microbial diversity of extreme environments without the need to bring samples to the lab for processing had been highlighted. Sample processing and sequencing had been included in the benefits of the field-deployable lab, and the Nanopore platform had been utilized.